Interpupillary and intercanthal distance values among females in AL-Qassim Region, KSA: A Cross-sectional study - Manal Abdalla Eltahir; Imtinan Alnasser; Shatha Aljaber (Wolters Kluwer Medknow Publications, 2024)
Introduction: Managing posttraumatic cranial, orbitofacial, and maxillofacial deformities. Furthermore, these values facilitate the correction of telecanthus associated with trauma, moreover, it is useful in dentistry for selection of the artificial teeth in the construction of dentures. Aim: The aim of this study was to measure interpupillary as well as ICD among the female Saudi population aged between 19 and 25 years. Materials and Methods: This cross‐sectional study was conducted at Qassim University/Dental Clinic. Female dental students/Qassim University were the population, sample size was 56 subjects. The examination was done in the dental chair while the participant was in an upright position and looking straight. The ruler and Vernier caliper were used to measure the IPD and ICD in millimeters. The records for each subject were taken by two examiners. Results and Discussion: Age as independent variable and ICD and IPD measure as dependent (outcome variables). Statistical analysis was done using (SPSS) software, for Windows (version 21; IBM, Armonk, New York). D: The data were shown as frequency, percentages, mean, and standard deviation, and P value is considered significant if it is >0.05. Conclusion: IPD and CD are affected by age in females. The value of studied females' subjects has been IPDs in the range of 52-64 mm and ICDs in the range of 24-37 mm. ICD is not half a distance of IPD in most of the studied subjects.